Linguistic features of aviation abbreviations and acronyms - Ergashova, Ra’no (The Lingua Spectrum, 2025)
This article provides a comprehensive analysis of the linguistic nature of abbreviations and acronyms used in the field of aviation, examining their formation mechanisms, structural-semantic features, and their role within the terminological system. Aviation abbreviations in English, Russian, and Uzbek are investigated through a comparative-linguistic approach, identifying their phonetic adaptation, morphological integration, graphemic variation, and processes of semantic specialization. The study also highlights the functional-pragmatic roles of abbreviations, such as speech economy, optimization of information capacity, and the facilitation of standardized data transmission. Special emphasis is placed on the role of international aviation organizations – ICAO, IATA, EASA, FAA, IFALPA and others in the global unification of abbreviation systems, coding standards, terminological coherence, and their regulatory significance in ensuring aeronautical safety. The article further analyzes stylistic differences in the use of aviation abbreviations in professional and non-professional contexts, sociolinguistic factors, and dynamic processes such as meaning narrowing and widening within discourse. Additionally, new scientific observations are presented regarding issues of equivalence in translation, semantic differentiation across languages, pragmatic adaptation, context-dependent shifts in meaning, and integration into national terminological systems. The study concludes with practical recommendations aimed at enhancing the effectiveness of abbreviation usage, improving standardization, and ensuring consistent normative application within language systems.